2021
DOI: 10.12845/sft.58.2.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Technical and Operational Parameters of Mobile Positive Pressure Ventilation Fans Used during Rescue Operations

Abstract: Aim: The aim of the article is to indicate the essential technical and operational parameters of mobile fans and to present the proposed testing method- ologies (as well as dedicated infrastructure) allowing to confirm the indicated features. Project and methods: In many places around the world, scientists conduct tests related to the use of mechanical tactical ventilation with the use of mobile positive pressure ventilation fans. These devices are used by fire protection units, among others, for the removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Rejecting the results for the two most unfavourable distances and tilt angles of the impeller axis (i.e., extreme maximum and minimum positions) in the analysis, the greatest reduction of the flow rate ranges from 5 to 19% depending on the fan type. The differences in the volume of air flow are related to the change in the flow direction (the collision with an obstacle in the form of a door opening frame) and the quality of the generated air stream 7 . According to Cimolino et al 17 changing the angle of the blown air can increase the flow rate by up to 30%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rejecting the results for the two most unfavourable distances and tilt angles of the impeller axis (i.e., extreme maximum and minimum positions) in the analysis, the greatest reduction of the flow rate ranges from 5 to 19% depending on the fan type. The differences in the volume of air flow are related to the change in the flow direction (the collision with an obstacle in the form of a door opening frame) and the quality of the generated air stream 7 . According to Cimolino et al 17 changing the angle of the blown air can increase the flow rate by up to 30%.…”
Section: Resultsmentioning
confidence: 99%
“…cars or garbage containers), ventilation of hard-to-reach places (where people stay)—with the use of electric fans 6 . Referring to devices (including positive pressure ventilators) used in rescue operations, it is indicated that they should be characterized by high operational reliability, efficiency, and functionality and should have little impact on the user 6 , 7 . In many countries, devices used in rescue operations are subject to special testing procedures 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the important role of rescue ventilators in the implementation of rescue operations, CNBOP-PIB (Scientific and Research Centre for Fire Protection—National Research Institute) in Józefów, Poland, has begun to implement the construction of a research infrastructure allowing the evaluation of the most important features determining the effectiveness of this type of equipment. Among the most important characteristics that can determine the effectiveness of rescue operations are: the size of the generated jet; the area of jet dispersion as a function of distance; noise; the length of operating time, as well as the weight and dimensions of the device 42 . The developed range of the apparatus is a flow tunnel made in accordance with the requirements of ANSI/AMCA 240-22 and PN-EN ISO 5801 43 , 44 .…”
Section: Introductionmentioning
confidence: 99%